Zmart for Empowerment Community Welfare - Sigit Priatmoko; Rahayu Lestari Putri (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
Zakat is one of the pillars that reflects Islam's great concern for human welfare. Islam considers that welfare can prevent people from disbelief. Therefore, poverty alleviation is also a concern in Islamic doctrines. Along with the development of science and technology, the management of zakat also continues to develop. The National Zakat Agency (BAZNAS) recently developed a Zmart program that aims to alleviate poverty by increasing mustahik-owned stalls or grocery stores' competitiveness. This study aims to examine the implementation of the Zmart program and the extent of its role in improving the welfare of the people who receive zakat (mustahik) in Bojonegoro Regency. Researchers used a descriptive qualitative method with a case study design. Data obtained through interviews, observation, and documentation. The informants in this study were the mustahik recipients of the Zmart program and the Chairperson of the BAZNAS in Bojonegoro Regency as the person in charge of implementing Zmart. The data analysis process uses an interactive model, which includes data collection, data reduction, data presentation, and concluding. The results showed that BAZNAS recently implemented Zmart in Bojonegoro Regency. The number of mustahik recipients is currently two from two remote villages in Margomulyo and Ngraho Districts. Zmart implementation went well according to the provisions. The existence of Zmart enough to help improve social and economic welfare. Mustahik is also starting to have a strategy to develop Zmart kiosks. However, it is not too significant because the Zmart business unit has just started. Also, BAZNAS Kabupaten Bojonegoro supports Zmart with a program to improve human resources quality yet, so mustahik competence in entrepreneurship is still low.